Biomimetic Syntheses of Amorfrutin C and C‐5 Substituted Amorfrutin Analogues. Issue 8 (11th February 2021) - Patel, Calum; Mies, Thomas; White, Andrew J. P.; Parsons, Philip J.; Barrett, Anthony G. M.
Abstract: Amorfrutin C, a C ‐5 prenyl amorfrutin, its allyl analog and an amorfrutin C ‐5 aldehyde have been synthesized using a biomimetic strategy from non‐aromatic precursors. In this approach, a dioxinone derived β, δ‐ diketo ester underwent a decarboxylative Pd(0) catalyzed prenyl migration to give a β, δ‐ diketo dioxinone, which readily aromatized giving the amorfrutin core. The introduction of prenyl and allyl moieties at the C ‐5 position of the scaffold was accomplished using a Claisen rearrangement. Alternatively, iodination, lithium‐iodine exchange and trapping with DMF gave the amorfrutin aldehyde and an amorfrutin alcohol when excess n ‐BuLi was used. Abstract : Amorfrutin C, a C ‐5 prenyl substituted amorfrutin, its allyl analog and an amorfrutin C‐5 aldehyde derivate have been synthesized from a common amorfrutin intermediate, which was prepared via a biomimetic β, δ ‐diketo‐dioxinone aromatization reaction.